A Systematic Review and Meta-Analysis of Randomized Controlled Trials With Novel Hormonal Therapies for Non-Metastatic Castration-Resistant Prostate Cancer: An Update From Mature Overall Survival Data - Maggi, Martina; Salciccia, Stefano; Del Giudice, Francesco; Busetto, Gian Maria; Falagario, Ugo G.; Carrieri, Giuseppe; Ferro, Matteo; Porreca, Angelo; Di Pierro, Giovanni Battista; Fasulo, Vittorio; Frantellizzi, Viviana; De Vincentis, Giuseppe; et al. (Frontiers in Oncology, 2021)
Introduction: To get better insight into the management of non-metastatic castration-resistant prostate cancer (M0 CRPC), in this meta-analysis and review we aimed to present an updated evaluation of the efficacy and safety of novel hormonal therapies (nHT) for M0 CRPC according to final analyses with mature overall survival (OS) and safety data. Methods: We analyzed metastasis-free survival (MFS), OS, time to prostate-specific antigen (PSA) progression, second-line therapies data, adverse events (AEs), including all AEs, serious AEs (SAEs), AEs leading to discontinuation of trial regimen, AEs leading to death, fatigue, dizziness, cardiovascular events, and fractures; moreover, we evaluated the impact of PSA doubling time (PSA-DT), Eastern Cooperative Oncology Group (ECOG) score, use of bone-targeted therapy, lymph lodes (LN) status, and prior HT on final OS data. A comparison among the placebo arms of the included trials in terms of survival and safety profiles was assessed. Results: According to the pooled analysis with updated and mature OS data, OS was significantly improved with nHT compared to placebo (hazard ratio (HR)= 0.74, 95% confidence interval (CI)= 0.66-0.84). nHT significantly improved OS over placebo across all pre-specified subgroups. Subgroup analysis revealed a greater OS benefit in patients with PSA-DT >6 months than 6months (HR= 0.69 versus HR= 0.75), ECOG 0 than 1 (HR= 0.70 versus HR= 0.80), N1 disease than N0 (HR= 0.61 versus HR= 0.78), and in those receiving bone-targeted therapy (HR= 0.65 versus HR= 0.74), and a comparable OS by number of prior HT (HR= 0.75 versus HR= 0.76, for HT= 1 and 2); yet, differences between pre-specified subgroups were not significant (all p> 0.05). Overall, the nHT arm was significantly associated with higher rates of AEs, when compared with the placebo arm. The long-term analysis showed a worse safety profile with nHT than the interim analysis. Conclusions: According to final analyses, nHT have shown to improve OS over placebo in the setting of high-risk M0 CRPC. The long-term analysis showed a worse safety profile with nHT than the interim analysis, whit distinct profiles among different nHT. The lack of survival data regarding second-line therapies remains a major issue.